In the quest of Hückel–Hückel and Hückel–Baird double aromatic tropylium (tri)cation and anion derivatives. (19th October 2022) - Escayola, Sílvia; Proos Vedin, Nathalie; Poater, Albert; Ottosson, Henrik; Solà, Miquel
Abstract: Besides the most common form of aromaticity involving a π‐ring, hexaiodobenzene and hexakis(phenylselenyl)benzene dications also present σ‐aromaticity in the outer ring formed by the main group substituents. These two compounds are considered σ‐ and π‐double aromatic, and their characterization is of special interest to the fields of organic and structural chemistry. In this work, we decided to explore the double aromaticity in substituted tropylium cations for three reasons: (i) the seven neutral halogen substituents of the tropylium cations will, without oxidation, lead to 14 σ‐electrons (a 4n + 2 Hückel number); (ii) tropylium cations are highly stable and can be easily generated experimentally; and (iii) whereas in substituted benzenes the distances between substituents in the optimized structures or X‐ray crystals are too large to allow strong σ‐aromaticity, these distances are expected to be shorter in substituted tropylium cations. Yet, instead of the expected σ‐aromaticity, we found that the most stable geometries are highly puckered, meaning that delocalization in both π‐ and σ‐systems is lost. Our results, which include also the tropylium anion and trication in the singlet and triplet state, show that there is a need to open a lone pair hole by oxidation to generate σ‐aromaticity. Among the systems studied, only triplet C7 Br7 +3 with an internal Hückel aromatic tropylium ring and an external incipient Baird aromatic Br7 ring shows double π‐ and σ‐aromaticity. This result, however, is functional‐dependent and reveals that 3 C7 Br7 3+ is at the borderline for onset of double aromaticity. Abstract : The triplet state of C7 Br7 +3, which features an inner Hückel aromatic tropylium ring and an outer weak Baird aromatic Br7 ring, exhibits double π‐ and σ‐aromaticity, according to the research we conducted on substituted tropylium cations and anions.